Antibacterial activities of synthesised Zno nanoparticles applied on reactive dyed batik fabrics. Issue 3 (4th March 2022) - Eskani, Istihanah Nurul; Astuti, Widi; Farida; Haerudin, Agus; Setiawan, Joni; Lestari, Dwi Wiji; Isnaini; Widayatno, Tri
Abstract: Batik is an Indonesian traditional cloth which has been recognised as an Intangible Cultural Heritage of Humanity by UNESCO for more than a decade. Batik cloth is popular among Indonesian people for daily use, both for formal and informal occasions. Commonly, batik cloth is made from cotton, which has many advantages, however prone to bacterial growth, particularly in the tropical climate. Therefore, it is important to develop batik cloth with antibacterial properties. The antibacterial properties of batik cloth were achieved by applying ZnO nanoparticles as antibacterial agent. The nanoparticles were synthesised using precipitation-sonication method. The formed ZnO nanoparticles were in an average particle size of 54.76 nm and 99.77% ZnO content. The batik making process utilized a synthetic reactive dye of remazol-turquoise blue. The effect of process sequence, the level of antibacterial properties, the morphology of the ZnO coated fabric, and the effect of the application of nanoparticle on the dyeing process were investigated. The results showed that ZnO nanoparticle application on the batik fabric led to antibacterial properties. The process sequences in adding the ZnO nanoparticles were confirmed to significantly affect the antibacterial effectivity and the colour strength. The application of ZnO nanoparticles did not affect the colour fastness to washing as the test showed similar value to that of without ZnO treatment. In addition, the application of ZnO nanoparticles affects the mechanical properties by increasing the tensile strength and decreasing the elongation at break. The application of ZnO after batik making process was shown to have a greater effect on the mechanical properties.